1972
DOI: 10.1126/science.175.4022.587
|View full text |Cite
|
Sign up to set email alerts
|

The Sulfur Cycle

Abstract: Even granting our uncertainties about parts of our model of the sulfur cycle, we can draw some conclusions from it: 1) Man is now contributing about one half as much as nature to the total atmospheric burden of sulfur compounds, but by A.D. 2000 he will be contributing about as much, and in the Northern Hemisphere alone he will be more than matching nature. 2) In industrialized regions he is overwhelming natural processes, and the removal processes are slow enough (several days, at least) so that the increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
120
0
3

Year Published

1974
1974
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 511 publications
(124 citation statements)
references
References 31 publications
1
120
0
3
Order By: Relevance
“…Lidar measurements have shown that the smaller particles are domainant near the top and bottom region of stratospheric aerosol layer (IWASKA, 1980), and same feature is found out also in other observations (BIGG, 1976;HOFMANN and ROSEN, 1977;GRAMS and LABY, 1978;FARLOW et al, 1979). The evaporation rate of H2SO4 estimated here on the basis of laser radar measurements cannot be neglected in the stratosphere in comparison with the production rate of sulfur compounds (5O2, COS, H2S, and so on) due to the transport into the stratosphere across the tropopause as suggested from numerical model calculations (LAZRUS and GANDRUD, 1974;HARRISON and LARSON, 1974;CRUTZEN, 1976) or from the analysis on stratospheric aerosol content, volcanic activity and so on (KELLOGG et al, 1972;JUNGE, 1974;LADLE, 1975).…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…Lidar measurements have shown that the smaller particles are domainant near the top and bottom region of stratospheric aerosol layer (IWASKA, 1980), and same feature is found out also in other observations (BIGG, 1976;HOFMANN and ROSEN, 1977;GRAMS and LABY, 1978;FARLOW et al, 1979). The evaporation rate of H2SO4 estimated here on the basis of laser radar measurements cannot be neglected in the stratosphere in comparison with the production rate of sulfur compounds (5O2, COS, H2S, and so on) due to the transport into the stratosphere across the tropopause as suggested from numerical model calculations (LAZRUS and GANDRUD, 1974;HARRISON and LARSON, 1974;CRUTZEN, 1976) or from the analysis on stratospheric aerosol content, volcanic activity and so on (KELLOGG et al, 1972;JUNGE, 1974;LADLE, 1975).…”
Section: Introductionsupporting
confidence: 66%
“…In many investigations (KELLOGG et al, 1972;JUNGE, 1974;LAZRUS and GANDRUD, 1974;HARRISON and LARSON, 1974;LADLE, 1975;CRUTZEN, 1976), the role of evaporation process of H2SO4 from sulfate particles in the global circulation of atmospheric sulfur has been left disregarded so far. However this evaporation may be an important secondary source of H2SO4 gas next to the photo-oxidative formation from sulfur compounds originated in the troposphere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gene groups that gave a significant variation in expression were selected from the genome-wide gene expression profile. 3,875 open reading frames, which induced commonly under different stress conditions, were extracted from the gene groups. We performed the hierarchical cluster analysis using GeneSpring.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Me 2 SO forms naturally from photooxidation of DMS in the atmosphere and from degradation of DMS by phytoplankton in the marine environment (2). Because Me 2 SO has low volatility and is highly hygroscopic, it is rapidly scavenged from the atmosphere by rain and returned to earth, and thereby plays a role in the global sulfur cycle (1,3).…”
mentioning
confidence: 99%